The Role of National Unity and Political Bodies in Handling Potential Conflicts in West Java Province - Nicholas, Alexander Lendie; Alexandra, Halomoan Freddy Sitinjak; Sukendro, Achmed; Widodo, Pujo; Saragih, Herlina Juni Risma (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to analyze the real role of the National Unity and Political Agency in Handling Potential Conflicts in West Java Province. This research uses qualitative research methods with data collection techniques in the form of interviews, observation and literature study, as well as data analysis using interactive models by Miles Huberman, Saldana (2014) and Role Theory according to Bruce J. Cohen (1992). The results of this research show that Bakesbangpol has issued West Java Governor Decree Number: 460.05/Kep.134-Bakesbangpol/2019 concerning the Integrated Team for Handling Regional Social Conflict in West Java Province as a follow-up to efforts to handle conflict. Conflict management carried out by Bakesbangpol in handling potential conflicts is through mediation and conciliation. In the context of successful conflict handling, West Java Bakesbangpol has applied the penta helix principle with a coordination, collaboration and synergy approach. Linked to role theory by Bruce J. Cohen (1992), Bakesbangpol has played a real role (Anacted Role) in resolving the polemic problem of establishing the construction of the Sang Hyang Hurip Santo Antonius Catholic Church in Bandung City. West Java Bakesbangpol also has a situation and condition monitoring application called "SIMBAKESBANGPOL" and a Whatsapp Group between Regency/City Bakesbangpol throughout West Java to find out up to date about conflict cases that occur in the West Java region as a whole.